Logistics costs of rice and soybean: Issues, challenges, and the impact of regulations - Adithya Prabowo; Muhamad Pudjianto (Center for Indonesian Policy Studies (CIPS), 2023)
This paper focuses on the challenges in the logistics of rice and soybeans in Indonesia. Rice distribution is complicated because rice production is concentrated in Java, while its consumption is high all over Indonesia. Soybeans are predominantly import and must contend with both import logistics and domestic logistics challenges. At the national level, logistics roughly contributes 21-23% of Indonesia's gross domestic product (GDP), much higher than in other developing countries. Transportation and inventory costs dominate logistics costs in Indonesia, while administrative costs such as fees and charges at the port contribute less than 6%. High logistics costs are passed on to consumers, raising the prices of goods, including staple foods.
Keywords: 330